Implementasi Good Corporate Governance (GCG) pada Pengukuran Resiko dan Kinerja Keuangan Bank Syariah: Studi Kasus Pada Bank Umum Syariah - Risma Warti; Dea Dara Audina; Adelia Azizi; Juliana Nasution (MES Bogor, 2023)
Good Corporate Governance (GCG) is one of the key elements in increasing economic efficiency that can help create a conducive and accountable relationship between elements of the company (board of commissioners, directors, and shareholders) in order to improve the company's financial performance. This study aims to determine the effect of Good Corporate Governance (GCG) as proxied by managerial ownership, institutional ownership, independent commissioners and sharia supervisory boards in measuring the risk of financial performance of Islamic banks in Indonesia. The results of this study as a whole can be concluded that, Good Corporate Governance (GCG) in measuring the risk and financial performance of Islamic banks has no significant effect.And to evaluate the concept of managing Islamic Commercial Banks in the implementation of Good Corporate Governance based on existing regulations on financial performance and financing risk at Islamic Commercial Banks in Indonesia which are registered with the Financial Services Authority. Keywords: GCG, Measurement Risk, Financial Performance, Islamic Banking.